PERBEDAAN HASIL BELAJAR MATEMATIKA SISWA SMP YANG BERKEPRIBADIAN EXTROVERT DAN INTROVERT PADA POKOK BAHASAN SISTEM PERSAMAAN LINIER - Azwar Habibi (FKIP Universitas Islam Jember, 2016)
The purpose of this research is to know the difference between students’ mathematic learning outcomes in junior high scholl between extrovert and introvert personality in mathematic linear equation material. The type of the research is experimental research with quantitative approach. The subject of this research is the eight grade students in junior high school who have extrovert and introvert personality. The data collecting methods are documentation and questionnaire. The results of the research are the value of t test = 5.082 and t table = 2.045 it’s mean that t tes > t table so Ha is accepted and Ho is rejected. Based on the data findings, it can be concluded that there is different of students’ mathematic learning outcomes in junior hight school between extrovert and introvert personality in the materials of mathematic linear equation system. The suggestion is that the teacher must be a motivator for students, and always care about the different personality of his/her students in order to find the best method or learning model that is comfortable to assist themto get good mathematic learning outcomes.Key Words: mathematic learning outcomes, extrovert and introvert personality